Combination of acellular dermal matrix with a de-epithelialised dermal flap during skin-reducing mastectomy and immediate breast reconstruction - Kankam, HKN (Ann R Coll Surg Engl, 2018)
INTRODUCTION: Patients with large ptotic breasts undergoing immediate implant-based reconstruction often require skin-reducing mastectomy to optimise the aesthetic outcome. However, healing complications, especially at the resulting inverted T-junction, leading to wound dehiscence, infection, skin necrosis, implant exposure and failed reconstruction have been widely reported. We present an innovative approach for immediate implant-based reconstruction combining porcine- or bovine-derived acellular dermal matrices with a de-epithelialised dermal sling to protect and support the implant, while improving clinical outcomes in this challenging group of patients. MATERIALS AND METHODS: Demographic, tumour and surgical data were reviewed for patients undergoing Wise pattern (T-scar) skin-reducing mastectomies with immediate implant-based reconstruction combining porcine- or bovine-derived acellular dermal matrices with a de-epithelialised dermal sling. RESULTS: This technique was successfully employed to reconstruct five large pendulous breasts in four breast cancer patients with a median age of 50.5 years (range 34–61 years) who were not suitable for, or had declined, flap-based reconstruction. The acellular dermal matrices used were SurgiMend®, Strattice(TM) and Braxon® and the expandable implants were placed in the sub-pectoral (n = 3) and pre-pectoral (n = 1) planes. The technical steps and clinical outcomes are presented. One patient experienced T-junction breakdown overlying the de-epithelialised dermis without implant loss. CONCLUSION: The combination of an acellular dermal matrix and a dermal sling provides a double-layer ‘water-proofing’ and support for the implants inferiorly, avoiding T-junction breakdown complications, since any dehiscence is on to well-vascularised dermis. Furthermore, the acellular dermal matrix stabilises the implant in the large mastectomy cavity (pocket control). This approach provides a viable option which facilitates mastectomy and immediate implant reconstruction in large-breasted patients.